MENERAPKAN PENGGUNAAN BAHAN AJAR BAGI GURU DI SMA NEGERI 3 OGAN KOMERING ULU - Ary Yanti Agustina (Jurnal Educative: Journal of Educational Studies, 2018)
This research was conducted in a class action SMA 3 OKU concerning the ability of teachers to implement the use of teaching materials. The formulation of the problem in research is how the teacher's ability by applying the use of teaching materials in SMP 9 Ogan Ogan Ulu. The study of this class action planned to take place in the second cycle of the meeting to each cycle 3 times meeting. The results showed that the frequency of planning is 64.67, the frequency of execution is 66.67 and frequency of assessment was 80.42. The researchers suggestion is to conduct quality improvement in implementing the use of teaching materials ranging from planning and implementation to the assessment so that teachers have the professional ability to perform the duties of professionalism, especially in the design and planning of teaching materials that will be given to students.